Topological structure of solution sets of differential inclusions: the constrained case - Wojciech Kryszewski (Abstract and Applied Analysis)
We survey and announce some current results on the existence, the viability, and the topological structure of the viable solutions of differential equations and inclusion in Banach spaces under set constraints. Some new results concerning semilinear differential inclusions with state variables constrained to the so-called regular and strictly regular sets, together with their applications, are presented and discussed.